Benzopyranone, benzophenone, and xanthone derivatives from the soil fungus Penicillium citrinum PSU-RSPG95 - Kongkiat Trisuwan (2018)
Two new benzopyranones, named coniochaetones E (1) and F (2), one new xanthone, penicillone C (3), and one new benzophenone, penicillanone (4), are isolated from the soil fungus Penicillium citrinum PSU-RSPG95, together with ten known compounds. Their structures are identified on the basis of spectroscopic data. The isolated compounds are evaluated for their cytotoxic activity. © 2014 Elsevier Ltd. All rights reserved.